2019
DOI: 10.1097/rli.0000000000000602
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Shear Wave Elastography of Neonatal and Infant Brains for Quantitative Evaluation of Increased Intracranial Pressure

Abstract: Objectives: Increased intracranial pressure (ICP) in neonates and infants is a severe disease state that requires adequate diagnosis and, depending on the clinical situation and whether it is increasing, a rapid and efficient therapy. Clinical evaluation, B-mode ultrasound, and Doppler ultrasound give rise to a basic noninvasive diagnosis of increased ICP. The purpose of this prospective study was 2-fold: first, to analyze the technical feasibility of obtaining shear wave elastography (SWE) measurements of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
20
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 33 publications
2
20
1
Order By: Relevance
“…However, our results differed from those presented by other authors 32–35 . Differences in the elasticity method (1‐ versus 2‐dimensional SWE) and the protocol used (different transducers, acquisition planes, ROI areas, and placements) might justify some of the observed differences (Table 3).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our results differed from those presented by other authors 32–35 . Differences in the elasticity method (1‐ versus 2‐dimensional SWE) and the protocol used (different transducers, acquisition planes, ROI areas, and placements) might justify some of the observed differences (Table 3).…”
Section: Discussioncontrasting
confidence: 99%
“…Studies on cerebral ultrasound elastography are scarce and mainly experimental 27–30 . There are few studies concerning the evaluation of the human neonatal brain, including strain elastography 31 and acoustic radiation force impulse elastography 32–35 . Although differences in normal values between authors exist, in term neonates, the thalamus has been reported to have higher elasticity values than the white matter.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is an expected observation as normal brain tissue on the contralateral side is compressed by the lesion (and its surrounding edema). A similar observation was made by Dirrichs et al, who detected significantly elevated values in children with hydrocephalus in comparison to a healthy control group [20].…”
Section: Discussionsupporting
confidence: 85%
“…Shear wave elastography (SWE) technology, as a newly developed elastic imaging technology, 12,13 can directly reflect the hardness of the tissue, by quantitatively analyzing the tissue hardness from the calculated absolute value of Young's modulus. By constructing a logistic regression model, this study aims to analyze the clinical variables of EC and AEH, transvaginal conventional ultrasonography and Young's modulus values, and assess the diagnostic value of SWE technology in perimenopausal and postmenopausal EC and AEH, in order to improve the accuracy for the diagnosis of EC and AEH.…”
Section: Introductionmentioning
confidence: 99%